Seeking Status, Forging Refuge: U.S. War Resister Migrations to Canada - Mountz, Alison (Refuge, 2020)
Often people migrate through interstitial zones and categories between state territories, policies, or designations like “immigrant” or “refugee.” Where there is no formal protection or legal status, people seek, forge, and find safe haven in other ways, by other means, and by necessity. In this article, I argue that U.S. war resisters to Canada forged safe haven through broadly based social movements. I develop this argument through examination of U.S. war-resister histories, focusing on two generations: U.S. citizens who came during the U.S.-led wars in Vietnam and, more recently, Afghanistan and Iraq. Resisters and activists forged refuge through alternative paths to protection, including the creation of shelter, the pursuit of time-space trajectories that carried people away from war and militarism, the formation of social movements across the Canada-U.S. border, and legal challenges to state policies and practices.